On boundary-value problems for generalized analytic and harmonic functions - Gutlyanskiĭ, V.Ya.; Nesmelova, O.V.; Ryazanov, V.I.; Yefimushkin, A.S. (Доповіді НАН України, 2020)
The present paper is a natural continuation of our last articles on the Riemann, Hilbert, Dirichlet, Poincaré, and, in particular, Neumann boundary-value problems for quasiconformal, analytic, harmonic functions and the so-called A-harmonic functions with arbitrary boundary data that are measurable with respect to the logarithmic capacity. Here, we extend the corresponding results to generalized analytic functions h : D→C with sources g:∂žh = g∈Lᵖ, p > 2, and to generalized harmonic functions U with sources G : ΔU=G∈Lᵖ, p > 2. Our approach is based on the geometric (functional-theoretic) interpretation of boundary values in comparison with the classical operator approach in PDE. Here, we will establish the corresponding existence theorems for the Poincaré problem on directional derivatives and, in particular, for the Neumann problem to the Poisson equations ΔU=G with arbitrary boundary data that are measurable with respect to the logarithmic capacity. A few mixed boundary-value problems are considered as well. These results can be also applied to semilinear equations of mathematical physics in anisotropic and inhomogeneous media. Робота є продовженням досліджень крайових задач Рімана, Гільберта, Діріхле, Пуанкаре і, зокрема, Неймана, для квазіконформних, аналітичних, гармонічних і так званих A-гармонічних функцій із довільними граничними даними, які є вимірюваними відносно логарифмічної ємності. Тут відповідні результати поширено на узагальнені аналітичні функції h : D→C з джерелом : g:∂žh = g∈Lᵖ, p > 2 , і на узагальнені гармонічні функції U з джерелом G ΔU=G∈Lᵖ, p > 2. Даний підхід заснований на геометричній (теоретико-функціональній) інтерпретації крайових задач у порівнянні з класичним операторним під ходом у теорії РЧП. Встановлені відповідні теореми існування для задачі Пуанкаре для похідної за напрямком і, зокрема, для задачі Неймана для рівняння Пуассона ΔU=G з довільними граничними даним и, що є вимірюваними відносно логарифмічної ємності. Також розглянуто декілька змішаних граничних задач. Ці результати можуть буть також застосовані до напівлінійних рівнянь математичної фізики в анізотропних та неоднорідних середовищах.